De l’indifférence à l’expérience d’une compassion interculturelle - Mathilde Mougin (Histoire, Médecine et Santé, 2022)
This article proposes to study the expression of travelers’ emotions when confronted with the spectacle of oriental torture in several 17th century travel accounts. If the violence of the treatment reserved for thieves and criminals is invariably noted by travelers in the East (the Ottoman Empire, Persia and Mughal India), the way in which they look at the patient of the torture varies from compassion to indifference. The aim of this article is to examine more specifically the political, axiological and anthropological implications of the expression of compassion by travelers, as well as those of their apparent indifference. In particular, we will consider the power of relativization of geographical and moral boundaries attached to this emotion. Our study will be based on the accounts of Jean-Baptiste Tavernier (1676) and Pierre-Martin de La Martinière (1674), two contemporaries who traveled to the East and who offer an abundant description of torture.